HUBUNGAN TINGKAT PENGETAHUAN TENTANG BUNDLE VENTILATOR ASSOCIATED PNEUMONIA TERHADAP PERILAKU PERAWAT DALAM PENCEGAHAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) DI ICU RSUD JAMPANGKULON - Mulya, Sandef Gesa; Safariyah, Erna; Tarwati, Kartika (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
Based on the RSUD Jampangkulon Medical Records, the number of ICU patients in January-October 2023 was 226 people with information about using ventilators. The number of days on ventilators in September was 20 patients with 4 cases of VAP, while in October 2023 there were 30 patients on ventilators with 7 cases of VAP. For cases with VAP, only 11 cases of VAP were obtained with culture results for A. Baumannii, Streptococcus, Pseudomonas Aeruginosa, Escherichia Coli. The general objective of this research is to determine the relationship between the level of knowledge about the VAP Bundle and the behavior of nurses in preventing VAP in the ICU at Jampangkulon Regional Hospital. This research method uses correlative analytics using a cross sectional design. Cross sectional design is a study that studies the relationship between risk factors (independent) and effect factors (dependent). A total of 17 people were taken with total sampling. The measuring instrument was a questionnaire and analyzed using Chi-square. Results: This research shows that nurses have good knowledge and good behavior. The results of the correlation coefficient test in this study showed that the value r=0.757 can be interpreted as p<0.05, so it can be concluded that there is a significant relationship between the level of knowledge and the behavior of nurses in preventing VAP. The conclusion of this research is that nurses with good knowledge are more numerous than fairly good knowledge as much as 41.2%. There were more nurses with good behavior than those with bad behavior, namely 64.7%. So, there is a relationship between the level of knowledge about the VAP bundle and VAP prevention behavior with a value of 0.757 is lower than 0,05.